Introduction to the special issue: Studying Populism, Religion and Media - a Nordic Perspective - Sumiala, Johanna (Nordic journal of religion and society, 2023)
This special issue contributes to the emerging research field of religion and populism in contemporary media contexts. With a shared focus on how Protestant Nordic contexts align with populist practices in specific ways, the articles provide illustrative examples of how the entanglement between religion, populism and media needs to be taken into account when dealing with contemporary public and political debates in the Nordics. The special issue is the result of collaborations among scholars in the Nordic Network on Media, Religion and Populism (NOREMPO). The NOREMPO research network was funded by the Nordic funding body NOS-HS (2021-2023). As an interdisciplinary network NOREMPO gathers Nordic scholars from Denmark, Finland, Norway and Sweden sharing special expertise in media studies, sociology of religion, the study of religion, political science, and computational social science.